Challenges and Opportunities in Managing Geriatric Depression: The Role of Personalized Medicine and Age-Appropriate Therapeutic Approaches - Agnieszka Jaros; Filip Rybakowski; Judyta Cielecka-Piontek; Magdalena Paczkowska-Walendowska; Bogusław Czerny; Adam Kamińki; Rasha Wafaie Mahmoud Elsorady; Agnieszka Bienert (MDPI AG, 2024)
The global aging population has experienced rapid growth in recent decades, leading to an increased prevalence of psychiatric disorders, particularly depression, among older adults. Depression in the geriatric population is often compounded by chronic physical conditions and various psychosocial factors, significantly impacting their quality of life. The main question raised in this review is as follows: how can personalized medicine and age-appropriate therapeutic approaches improve the management of geriatric depression? This paper explores the epidemiology of geriatric depression, highlighting the influence of gender, race, and socioeconomic status on its prevalence. The classification and diagnosis of geriatric depressive disorders, based on ICD-11 and DSM-5 criteria, reveal the complexity of managing these conditions in older adults. Personalized medicine (PM) emerges as a promising approach, focusing on tailoring treatments to the individual's genetic, clinical, and environmental characteristics. However, the application of PM in this demographic faces challenges, particularly in the context of pharmaceutical forms. The need for age-appropriate drug delivery systems is critical, given the prevalence of polypharmacy and issues such as dysphagia among the older patients. This study emphasizes the importance of developing patient-centric formulations to enhance the effectiveness of personalized therapy in geriatric patients.